2022
DOI: 10.1371/journal.pone.0266454
|View full text |Cite
|
Sign up to set email alerts
|

KLF11 deficiency enhances chemokine generation and fibrosis in murine unilateral ureteral obstruction

Abstract: Progression of virtually all forms of chronic kidney disease (CKD) is associated with activation of pro-inflammatory and pro-fibrotic signaling pathways. Despite extensive research, progress in identifying therapeutic targets to arrest or slow progression of CKD has been limited by incomplete understanding of basic mechanisms underlying renal inflammation and fibrosis in CKD. Recent studies have identified Kruppel-like transcription factors that have been shown to play critical roles in renal development, home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Among the PBMC common hub genes, several genes have been reported to be associated with kidney disease or hematologic disorder. KLF11 is a Krüppel-type zinc finger protein whose deficiency enhances chemokine generation and fibrosis in murine unilateral ureteral obstruction (27) and highly induced by TGF-b (28). It has been reported that KLF11 inhibits the activity of SMAD7 and enhances TGF-b pathway activation (29), through which KLF11 may influence the lymphocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…Among the PBMC common hub genes, several genes have been reported to be associated with kidney disease or hematologic disorder. KLF11 is a Krüppel-type zinc finger protein whose deficiency enhances chemokine generation and fibrosis in murine unilateral ureteral obstruction (27) and highly induced by TGF-b (28). It has been reported that KLF11 inhibits the activity of SMAD7 and enhances TGF-b pathway activation (29), through which KLF11 may influence the lymphocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…As a zinc-finger transcription factor, KLF11 is involved in the regulation of various pathophysiological processes, such as growth, development, fibrosis, and inflammatory response. 5 For instance, KLF11 was reported to protect against cardiac hypertrophy and fibrosis in mice. 6 A recent study reported the differential expression of KLF11 in the OA cartilage specimens.…”
mentioning
confidence: 99%
“…Interestingly, De Lorenzo et al . have just demonstrated that KLF11 reduces chronic kidney injury (unilateral ureteral obstruction) by inhibiting the TGF- β 1/Smad3 pathway (10).…”
mentioning
confidence: 99%
“…We thus hypothesize that KLF11 protects against IRI because it suppresses renal production of ET-1 and inflammation. Interestingly, De Lorenzo et al have just demonstrated that KLF11 reduces chronic kidney injury (unilateral ureteral obstruction) by inhibiting the TGF-b1/Smad3 pathway (10).…”
mentioning
confidence: 99%